LEKSIKON NAMA TUMBUHAN DALAM PERIBAHASA MASYARAKAT MELAYU KETAPANG - Winda Fitriani; Ahmad Rabi’ul Muzammil; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract  This research was motivated by the aim of researchers to describe the types of proverbs, lingual unit forms, and types of meanings. Researchers used proverb theory, types of meanings, lingual, semantic unit types and types of meanings to uncover the problems that exist in this study. The problems in this studied were the types of proverbs, lingual unit forms, types of meanings, and supplementary Indonesian learning texts in the 2013 class X curriculum. Based on research, the researches succeeded in found 46 plant lexicons from 37 proverb of Ketapang Malay community. The proverb were grouped by type, there was 23 of parable, the maxim was ten, and the phrase was four. Plant lexicon in Ketapang Malay proverb there were three forms of lingual units, namely monomorphemis (single word) totaling 28, polymorphemis (derivative words) the form of affixation of five words, and the form of thirteen phrases. The lexicon of plants name contained in these proverb can be use as teaching material for student in class X Indonesian Language lesson with material on the observation report. Keywords: ethnolinguistic, Ketapang Malay proverb, plants lexicon